THE PERSPECTIVES OF EFFECTIVELY USE THE LATEST INFORMATIONAL COMMUNICATIONAL TECHNOLOGIES IN MEDICAL INSTITUTIONS OF THE MINISTRY OF INTERNAL AFFAIRS - Z.S.Jumanov (International Journal of Innovations in Engineering Research and Technology, 2021)
The perspective of effective using the modern informational communicational technologies in medical institutions of the Ministry of Internal Affairs and information about the using the regulation acts and documents on realization it and working out new software were given in this article. Besides that, here given the latest informational communicational technologies for realization in the medical institutions of the Ministry of Internal Affairs.